pncA mutations in pyrazinamide-resistant Mycobacterium tuberculosis isolates in Portugal - Portugal, I (2015)
The nucleotide sequences of the pncA genes within 55 multidrug-resistant pyrazinamide-resistant Mycobacterium tuberculosis clinical isolates were determined. Fifty-three out of the 55 isolates were pyrazinamidase (PZase) negative. Four strains contained a